Increased E-commerce and Fintech Transactions During the Covid-19 Pandemic - Ayunda Putri Nilasari; Retnosari Retnosari; Endang Kartini Panggiarti; Erni Puji Astutik (Universitas Muhammadiyah Magelang, 2022)
Activity restrictions to suppress the spread of the Covid-19 virus have made people take advantage of existing technology as well as the emergence of e-commerce and the ease of transactions creating business opportunities that greatly assist people in meeting their needs without having to leave the house and interact with many people. Researchers want to know the influence of the development of fintech, e-commerce, delivery services, lifestyle and banking security on meeting the online needs of the millennial community among students. The research method used is quantitative research with a sample of millennial society from Tidar University and Stekom University students. Various e-commerce applications, social media, fintech and online transportation are the most widely used by respondents 94.2% shoppe, 49.7% whatsapp and grab. Technological sophistication affects lifestyle in meeting needs during the pandemic because more than 75% answered agree and 45% strongly agreed. The lifestyle of today's society by utilizing technology becomes faster, more effective and efficient because more than 75% answered agree and 50% answered strongly agree. Respondents from Tidar University and Stekom University operate e-commerce applications that are available by taking advantage of the ease of transactions, 90% agree. The results of student responses to promos or free shipping coupons made them interested in making online purchases, 80% answered strongly agree. The results of the survey of student respondents regarding the security and ease of payment from banking services to conduct transactions either through e-banking or top up answered 75% agreed.